THE DEVELOPMENT OF WORD CLUSTER - Khaydarova Nigora; Abdukhalimova Gulshoda (TADQIQOTLAR, 2025)
Annotation: This article explores the historical and theoretical development of word  clusters,  highlighting  their  significance  in  linguistic  theory  and  practical applications  such  as  computational  linguistics,  natural  language  processing,  and language  education.  The  research  traces  the  evolution  of  the  concept  from  early linguistic grouping practices to modern algorithmic approaches that leverage statistical and semantic analysis. Particular attention is given to the methodology of cluster formation, types of clustering  algorithms,  and  the  impact  of  word  clusters  on  enhancing  machine understanding of human language. The study also addresses the pedagogical value of word  clusters  in  vocabulary  acquisition  and  cognitive  linguistics.  The  findings underline that the development of word clusters has been both a reflection of linguistic theory and a tool that continues to shape it.